How to fail : everything I've ever learned from things going wrong - Day, Elizabeth (London : 4th Estate, 2009)
This is a book for anyone who has ever failed. Which means it$1 (Bs a book for everyone. If I have learned one thing from this shockingly beautiful venture called life, it is this: failure has taught me lessons I would never otherwise have understood. I have evolved more as a result of things going wrong than when everything seemed to be going right. Out of crisis has come clarity, and sometimes even catharsis. Part memoir, part manifesto, and including chapters on dating, work, sport, babies, families, anger and friendship, it is based on the simple premise that understanding why we fail ultimately makes us stronger. It's a book about learning from our mistakes and about not being afraid.s
Keywords: Self-realization.; Failure (Psychology).